Targeted delivery of doxorubicin into tumor cells by nanostructured lipid carriers conjugated to anti-EGFRvIII monoclonal antibody. (2nd January 2018) - Abdolahpour, Saeideh; Toliyat, Tayebeh; Omidfar, Kobra; Modjtahedi, Helmout; Wong, Albert J.; Rasaee, Mohammad Javad; Kashanian, Susan; Paknejad, Maliheh
Abstract: Epidermal growth factor receptor variant III (EGFRvIII) is the most common variant of the EGF receptor in many human tumors. This variant is tumor specific and highly immunogenic, thus, it can be used as a target for targeted drug delivery toward tumor cells. The major aim of this study was to develop an EGFRvIII-mediated drug delivery system by anti-EGFRvIII monoclonal antibody (MAb) conjugated to doxorubicin (Dox)-loaded nanostructured lipid carriers (NLC) to enhance the targeting specificity and cytotoxic effect of Dox on EGFRvIII-overexpressing cell line. In our study, Dox was chosen as a hydrophobic cytotoxic drug and drug-loaded nanostructured lipid carriers (Dox-NLC) was prepared by solvent emulsification/evaporation method. In order to conjugate anti-EGFRvIII MAb to Dox-NLC, DSPE-PEG2000-NHS (1, 2-distearoylphosphatidylethanolamine–polyethylene glycol 2000–NHS) was used as a linker. Physicochemical characteristics of antibody conjugated Dox-NLC (MAb-Dox-NLC), including particle size, zeta potential, entrapment efficiency and in vitro Dox release were investigated. Cytotoxicity of MAb-Dox-NLC against NIH-3T3 and HC2 20d2/c (EGFRvIII-transfected NIH-3T3) cell lines was evaluated. The MAb-Dox-NLC appeared to enhance the cytotoxic activity of targeted NLC against HC2 20d2/c cells. The cellular uptake percentage of targeted NLC by HC2 20d2/c cells was higher than that of NIH-3T3 cells, indicating that EGFRvIII can specifically target HC2 20d2/c cells. In conclusion, anti-EGFRvIII MAb-targeted NLC may be considered as an effective nanocarrier for targeted drug delivery.